Artificial light at night causes diapause inhibition and sex‐specific life history changes in a moth - Geffen, Koert G.; Grunsven, Roy H. A.; Ruijven, Jasper; Berendse, Frank; Veenendaal, Elmar M. (Ecology and evolution, 2014)
Rapidly increasing levels of light pollution subject nocturnal organisms to major alterations of their habitat, the ecological consequences of which are largely unknown. Moths are well‐known to be attracted to light at night, but effects of light on other aspects of moth ecology, such as larval development and life‐history, remain unknown. Such effects may have important consequences for fitness and thus for moth population sizes. To study the effects of artificial night lighting on development and life‐history of moths, we experimentally subjected Mamestra brassicae (Noctuidae) caterpillars to low intensity green, white, red or no artificial light at night and determined their growth rate, maximum caterpillar mass, age at pupation, pupal mass and pupation duration. We found sex‐specific effects of artificial light on caterpillar life‐history, with male caterpillars subjected to green and white light reaching a lower maximum mass, pupating earlier and obtaining a lower pupal mass than male caterpillars under red light or in darkness. These effects can have major implications for fitness, but were absent in female caterpillars. Moreover, by the time that the first adult moth from the dark control treatment emerged from its pupa (after 110 days), about 85% of the moths that were under green light and 83% of the moths that were under white light had already emerged. These differences in pupation duration occurred in both sexes and were highly significant, and likely result from diapause inhibition by artificial night lighting. We conclude that low levels of nocturnal illumination can disrupt life‐histories in moths and inhibit the initiation of pupal diapause. This may result in reduced fitness and increased mortality. The application of red light, instead of white or green light, might be an appropriate measure to mitigate negative artificial light effects on moth life history. Artificial night lighting is a widespread and continuously growing phenomenon, with largely unknown consequences for nocturnal organisms. It is well‐established that moths are strongly attacted to light, but artificial light effects on other aspects of moth ecology remain poorly studied. Here, we show that effects of artificial light at night extend far beyond attraction: life‐history of moths may be disturbed, and light at night can interefere with daylength as a cue for initiaton of pupal diapause.